EXPERIMENTAL STUDY ON CRACK AND DEFORMATION IN REINFORCED CONCRETE BEAMS USING DIGITAL IMAGE CORRELATION - Didar Meiramov; Huynjin Ju; Hae-Chang Cho (Journal of Mechanics of Continua and Mathematical Sciences, 2025)
The evaluation of cracking and displacement in reinforced concrete beams is critical for assessing structural performance and stiffness during service. The effectiveness of the digital image correlation (DIC) method was investigated for evaluating cracks and displacements in reinforced concrete beams. The beams had varying reinforcement ratios and concrete covers as key parameters. Specimens were tested under two-point loading, and the results were recorded using traditional measurement instruments. These results were then compared with the DIC results. The findings demonstrate that the DIC method accurately determines midspan deflection, with a minor error of 2.33% compared to traditional measuring instruments. However, the accuracy of crack width measurements varied due to elastic deformation, with errors ranging from 7.41% to 68% compared to those obtained by crack detectors. These results demonstrate the potential of the DIC method as a reliable tool for detailed analysis of cracking and deformation in reinforced concrete structures, though further refinement may be required for crack width assessment.